The Multidimensionality of Legal Facts - Shafalovich, Hanna (Teisė, 2021)
This article explores the multidimensionality of legal facts in their various aspects, which are considered atypical in “mechanical jurisprudence.” As a result of the research, the author concludes that the multidimensionality of legal facts is represented by actual, legal and terminological, behavioral, documentary, and other aspects.
Keywords: theory of legal facts; mechanical jurisprudence; quantum-physical approach; methodology; multidimensionality; multilevelness